# Câu 23 trang 205 SGK Đại số và Giải tích 11 Nâng cao

##### Hướng dẫn giải

a. $$y' = {{2\left( {{x^2} - 5x + 5} \right) - \left( {2x + 3} \right)\left( {2x - 5} \right)} \over {{{\left( {{x^2} - 5x + 5} \right)}^2}}} = {{ - 2{x^2} - 6x + 25} \over {{{\left( {{x^2} - 5x + 5} \right)}^2}}}$$

b. $$y' = {{ - 5{{\left( {{x^2} - x + 1} \right)}^4}\left( {2x - 1} \right)} \over {{{\left( {{x^2} - x + 1} \right)}^{10}}}} = {{ - 5\left( {2x - 1} \right)} \over {{{\left( {{x^2} - x + 1} \right)}^6}}}$$

c. $$y' = 2x + \sqrt x + x.{1 \over {2\sqrt x }} = 2x + {3 \over 2}\sqrt x$$

d.

\eqalign{ & y' = {\left( {x + 2} \right)^2}{\left( {x + 3} \right)^2} + \left( {x + 1} \right).2\left( {x + 2} \right){\left( {x + 3} \right)^3} + \left( {x + 1} \right){\left( {x + 2} \right)^2}3{\left( {x + 3} \right)^2} \cr & = 2\left( {x + 2} \right){\left( {x + 3} \right)^2}\left( {3{x^2} + 11x + 9} \right) \cr}

e. $$y = \sqrt {x + {1 \over x}} \Rightarrow y' = {{1 - {1 \over {{x^2}}}} \over {2\sqrt {x + {1 \over x}} }} = {{{x^2} - 1} \over {2{x^2}\sqrt {{{{x^2} + 1} \over x}} }}$$